A silver-catalyzed [3 + 3]-annulation cascade of alkynyl alcohols and α, β-unsaturated ketones for the regioselective assembly of chromanes. Issue 3 (5th January 2022) - Nakate, Ashwini K.; Thorat, Sagar S.; Jain, Shailja; Rama Krishna, Gamidi; Vanka, Kumar; Kontham, Ravindar
Abstract : An unprecedented Ag(i )-catalyzed [3 + 3]-annulation of alkynyl alcohols (5-hexyn-1-ols) and α, β-unsaturated ketones is reported to construct simple to complex chromanes. Abstract : An unprecedented Ag(i )-catalyzed [3 + 3]-annulation of alkynyl alcohols (5-hexyn-1-ols) and α, β-unsaturated ketones is reported to construct simple to complex chromanes. This transformation begins with hydroalkoxylation of alkynol through C–C triple bond activation to give cyclic-enol ether, followed by intermolecular 1, 4-addition and intramolecular 1, 2-addition of enol ethers onto the enone and oxidative aromatization or Grob-type elimination steps. Facile reaction conditions, broad substrate scope, good to excellent yields, and atom economy are the salient features of this protocol. Isolation of the active pyran-tethered cyclohexadiene reaction intermediate, additional supporting experiments, and DFT calculations strongly support the experimental findings and corroborate our proposed mechanism.